1970
DOI: 10.1111/j.1151-2916.1970.tb12073.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth in the System PbO‐B2O3

Abstract: The temperature dependence of the rate of growth of PbO/2B2O3 from lead borate melts with PbO/B2O3 mole ratios of 1/3,1/2, 2/3, and 1 was determined. The maximum growth rates occurred from those melts which contained a slight excess of PbO. The results are explained on the basis of a modification in the structure of the melt in the interfacial zone as the PbO content is changed. Such changes markedly affect the fluidity of the melt, alter the concentration of crystallizable species, and may reduce the driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Moreover, with the decrease of cooling rate, the fine perovskite crystals with characteristic of dispersing spicule gradually changed to the larger dendrites and equiaxed crystals, and the precipitation amount of perovskite crystals also increased significantly, which was consistent with the results of Zhang et al 12 and Eagan. 18 This indicated that with decreasing of the cooling rate, the reaction time of Ca 2+ and TiO 3 2− extended, and thus both the self-growth and the grain coarsening of perovskite crystals were promoted.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, with the decrease of cooling rate, the fine perovskite crystals with characteristic of dispersing spicule gradually changed to the larger dendrites and equiaxed crystals, and the precipitation amount of perovskite crystals also increased significantly, which was consistent with the results of Zhang et al 12 and Eagan. 18 This indicated that with decreasing of the cooling rate, the reaction time of Ca 2+ and TiO 3 2− extended, and thus both the self-growth and the grain coarsening of perovskite crystals were promoted.…”
Section: Resultsmentioning
confidence: 94%
“…12 and Eagan. 18 This indicated that with decreasing of the cooling rate, the reaction time of Ca 2+ and TiO 3 2− extended, and thus both the self-growth and the grain coarsening of perovskite crystals were promoted.
2 Vertical section of the sample obtained in a normal-gravity field at a cooling rate of 1 K min −1
3 Micrographs of the samples obtained in a normal-gravity field at different cooling rates: a α = 6 K min −1 , b α = 3 K min −1 , c α = 2 K min −1 , d α = 1 K min −1
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation